Non-Reacting Spray Characteristics of Gasoline and Diesel With a Heavy-Duty Single-Hole Injector - Tzanetakis, Tom; Johnson, Jaclyn; Schmidt, Henry; Atkinson, William; Naber, Jeffrey (Frontiers in Mechanical Engineering, 2022)
The non-reacting spray characteristics of two gasoline-like fuels were studied and compared to ultra-low-sulfur diesel (ULSD). These fuels shared similar physical properties and were thus differentiated based on research octane number (RON). Although RON60 and RON92 had different reactivity, it was hypothesized that they would exhibit similar non-reacting spray characteristics due to their physical similarities. Experiments were conducted in an optically accessible, constant-volume combustion chamber using a single-hole injector representing high-pressure, common-rail fuel systems. Shadowgraph and Mie-scattering techniques were employed to measure the spray dispersion angles and penetration lengths under non-vaporizing and vaporizing conditions. Gasoline-like fuels exhibited similar or larger non-vaporizing dispersion angle compared to ULSD. All fuels followed a typical correlation based on air-to-fuel density ratio indicating that liquid density is the main fuel parameter. Injection pressure had a negligible effect on dispersion angle. Gasoline-like fuels had slower non-vaporizing penetration rates compared to ULSD due to their larger dispersion. As evidenced by the collapse of data onto a non-dimensional penetration correlation, all fuels conformed to the expected physical theory governing non-vaporizing sprays. There was no significant trend in the vaporizing dispersion angle with respect to fuel type which remained relatively constant across the charge gas temperature range of 800-1200 K. There was also minimal difference in vapor penetration across fuels and charge temperature. The liquid length of gasoline-like fuels was much shorter than ULSD and exhibited no dependence on charge temperature at a given charge gas pressure. This behavior was attributed to gasoline being limited by inter-phase transport as opposed to mixing rate during evaporation. RON92 had a larger non-vaporizing dispersion angle but similar penetration compared to RON60. Although this seems to violate the original similarity hypothesis, the analysis was made difficult due to the use of different injector builds. However, RON92 did show a slightly larger vapor dispersion angle than RON60 and ULSD. This was attributed to nuanced volatility differences between the gasoline-like fuels and indicates that vapor dispersion likely relies on a more complex correlation beyond just the air-to-fuel density ratio. Finally, RON92 showed the same quantitative liquid length and insensitivity to charge gas temperature as RON60.